Neurolinguistic Programming, Gender Perspective and Witness Evidence - Miranda Verdú, Beatriz (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The main purpose of this paper is to demonstrate that certain tools and techniques of Neurolinguistic Programming are useful for members of the judicial career in the taking of evidence, in particular in the case of victims of gender violence or crimes against sexual freedom. Various tools of language and communication analysis in the taking of witness evidence in criminal hearings allow us to decode information provided by the victim as well as to reframe a conflict situation, and thus to take into account the perspective of gender. As a result, communication is more effective, which contributes to a more human justice.